P47 A case of parenchymal nodular amyloidosis with Sjögren's syndrome mimicking a bronchogenic tumour. (20th April 2020) - Halai, Kapil; Savanovic-Abel, Ognjenka; Howell, Timothy
Abstract: Background: Amyloidosis is a disorder characterised by the misfolding of extracellular proteins. Patients with Sjögren's syndrome frequently have a range of lung manifestations. Parenchymal nodular amyloidosis has been reported in association with Sjögren's syndrome although occurrences are rare. Methods: We present a 77 year old woman with a longstanding history of exertional breathlessness on a background of mild asthma since childhood, a cardiac pacemaker for atrial fibrillation and sick sinus syndrome. She has never smoked tobacco and has a good performance status. She presented with an episode of breathlessness and cough requiring hospital admission, receiving treatment for a lower respiratory tract infection. Results: Chest X-rays had suggested two benign nodules in the right upper lobe which seemed to have progressed over the last ten years. Amongst her inpatient investigation, she underwent a CT-pulmonary angiogram which did not demonstrate a pulmonary embolism but found three lesions in the right upper lobe. The largest of the lesions measured 2.4cm in size and was suspicious for malignancy. A PET-CT scan showed two of these to be calcified lesions in the right upper lobe, and the other an irregular soft tissue density nodule with low-grade FDG uptake, suspicious of a primary bronchogenic tumour. Lung function showed mild airflow obstruction. Bronchoscopy and endobronchial ultrasound-guided biopsy did not yield a diagnosis. As surgery could be potentially curative, she underwent a right upper lobectomy and systematic nodal sampling. The histology on the lesions has shown abundant eosinophilic concretions with peripherally prominent foreign body giant cell reaction. This was congophilic and showed green birefringence. Further staining suggested AL amyloid. Histological appearances and the clinical picture seemed to represent parenchymal nodular amyloidosis. Further investigation revealed ANA was 1:640 speckled pattern and anti-Ro antibody positive. On further questioning, she reported sicca symptoms affecting eyes and mouth, fatigue and generalised arthralgia particularly affecting knees, ankles, wrist and shoulder. Schirmer's test suggested severely dry eyes. A diagnosis of primary Sjögren's was made and hydroxychloroquine was started. Conclusion: Parenchymal nodular amyloidosis has been associated with Sjögren's syndrome but is a rare manifestation. However, there are other chronic inflammatory or haematological condition has been described. Parenchymal nodular amyloidosis is associated with multiple nodules, rarely a single nodule. Isolated pulmonary amyloidosis has four distinct patterns of presentation: diffuse alveolar septal, lymphatic, trachea-bronchial and nodule-parenchymal (typically found incidentally on routine imaging). These nodules remain stable over long periods of time. There is no curative treatment of nodular amyloid, but successful treatment has been documented with resection or laser therapy. In our patient, the presence of AL amyloidosis prompted us to investigate for an underlying cause and clinical features and immunological testing suggested primary Sjögren's and should be considered in the pulmonary manifestation of this condition. Disclosures: K. Halai None. O. Savanovic-Abel None. T. Howell None.